Provocări şi dileme în educarea copiilor cu dizabilităţi - Ciobanu Grasu, Mihaela (Calitatea Vieții, 2012)
One of the most vulnerable categories of population are children with disabilities. In order to achieve their further social inclusion, the focus is on quality education and their recovery. Through a qualitative approach, semi-directive interviews applied to relevant stakeholders, we have identified the main challenges and dilemmas faced by professionals, in terms of finding the best solutions for the identification, the assessment and the education of these children.